An unusual aetiology of solitary rectal ulcer syndrome - Ząber, Aldona; Kucharski, Jakub; Zapała, Brygida; Konys, Justyna; Banasiuk, Marcin; Banaszkiewicz, Aleksandra (Pediatria Polska - Polish Journal of Paediatrics, 2022)
Solitary rectal ulcer syndrome (SRUS) is a rare condition, usually affecting young adults, with few cases in children. Solitary rectal ulcer syndrome appears in the mucosa of the large intestine, typically the rectum, and has the form of singular or multiple lesions – most commonly ulcerations. Its aetiology remains unclear. However, there are some theories explaining its onset. The disease can manifest, e.g., as a rectal bleeding, mucoid discharge or abdominal pain. There is a particular constellation of features in the histopathological examination that confirms the diagnosis of SRUS. In spite of the fact that there are many pharmacological and non-pharmacological forms of treatment, managing SRUS remains unsatisfactory. The paper describes a case of a patient with a very unusual cause of SRUS – tailgut cyst. It is reported to raise the awareness of such a disease and emphasize the importance of further testing when the treatment fails.